Avaliação externa de curso de graduação e os procedimentos de qualificação dos acervos em uma instituição federal de ensino superior - Alves, Regycléia Botelho Cutrim (2014)
It analyzes procedures of graduation courses with the library for collection qualification in External Evaluation. It uses as theoretical framework the higher education regulatory mark and the legislation of the National Evaluation System of Higher Education SINAES, particularly the courses external evaluation process. The instruments developed by INEP in the external evaluation process, indicators and concepts are the references used to identify the procedures that to reach the satisfactory concept. The used methodology is the case study, characterized as a quantitative and qualitative study. As techniques for collecting qualitative data, we used document analysis of the courses evaluation reports for reapproval in the last three years, and interviews with the researched subjects; and for quantitative data collection, we used questionnaires which were applied to the population represented by the teachers of the researched Higher Education Institution. It is concluded that the procedures adopted by the graduation courses of the Higher Education Institution are developed independently in each department, so there are gaps to be solved in three of the researched courses in order to get course qualification. On the other hand, when there is integration between the courses and the library, the collection qualification and its evaluation achieve satisfactory review concepts both in the institution s and INEP s evaluation.